High-risk students talking low-stakes assessments: Do the data reflect ability or effort? - Reed, Deborah; Hall, S. Ryan; Houchins, David E. (Forum Pedagogiczne, 2024)
This exploratory study examined whether test-taking effort (TTE) might be a concern in monthly low-stakes testing of juvenile offenders’ (n = 50) reading abilities. Among the graphs of 10 randomly selected students’ scores, 6 showed large fluctuations in performance from administration to administration, and another 2 showed precipitous declines across time. For the full sample, most of the average changes in scores from month-to-month far exceeded the standard error of measurement and equated to a 1- to 3-grade-level difference in how students’ reading performance could be interpreted. These changes could be positive or negative and varied within and across students. Most of the average testing times were below the expected minimum of 5 min, but total testing time generally was not correlated with scores. Given the response validity concerns, recommendations are made for supporting TTE.